Analisis Penerapan Sak Etap Dalam Penyusunan Laporan Keuangan Koperasi ( Studi Kasus Pada KOPKAR PDAM Tirta Sanita ) - Nurdiansyah, Hadi; Setiawan, Hendra (Jurnal Ilmiah Akuntansi Kesatuan, 2016)
The purpose of this study is to analyze the application of IFRSs in the preparation of financial statements ETAP cooperatives, especially Cooperative Tirta Sanita. Analysis is performed to determine whether the financial statements have been applied by the Cooperatives is in accordance with GAAP ETAP set since July 2010. The analysis conducted in this study uses a descriptive method while selected data sources are secondary data from financial statements. The selected data collection procedures are obtained form library research, literatures, records, field research and interviews. The results showed that the Cooperative Tirta Sanita has been making adjustments in applying SAK ETAP in the preparation of its financial statements, but still not all the adjustments in the SAK ETAP have been applied in the preparation of its financial statements. This is evident with the availability of financial statements consisting of a balance sheet, profit/loss, change in equity, and cash flow statement. Cooperative Tirta Sanita using SAK ETAP with reporting guidelines still largely the same as before adopting IFRS GAAP General, therefor not too many significant changes occured. In other words, there was no significant effect happens on the application of GAAP in the financial statements Cooperative ETAP Tirta Sanita. Thus, financial statement reporting guidelines Cooperative Tirta Sanita with SAK ETAP is still using the principles of the historical cost method uses a different cost with SFAS General that is currently adopting IFRS using the fair value method. In general, this is the fundamental difference for the implementation of SAK ETAP.